Effect of one point mutation on protein structure - Salleh, Abu Bakar; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Leow, Adam Thean Chor; Tejo, Bimo Ario; Mohd Ali, Mohd Shukuri; Abd Rahim, Arilla Sri Masayu; Zakaria, Norhayati; Raja Abdul Rahman, Raja Noor Zaliha (2012)
The role of each amino acid in a protein sequence towards protein function has been continuously studied. A single point mutation can occur spontaneously and naturally in nucleotide replication. However, it is possible to get specific single point mutation via site directed mutation. Earlier we studied, one point mutation on FI protease. The mutant W200R and D58S showed the importance of ion pairs and secondary structure towards conformational stability of the FI protease. Studies on L2 lipase, with mutation at Ser2 to Phe2, located at the N-terminal resulted in the alteration of the optimal temperature and pH. The analysis showed that S2F mutation was not directly involved in catalysis since there was no changes in the substrate specificity. In another work, mutation from ARM lipase RI57S showed an increase in temperature stability but the S236R mutant showed the reverse effect. Apparently single point mutation can influence the conformational structure and properties of protein.